Which equation can be used to represent “six added to twice the sum of a number and four is equal to one-half of the difference of three and

Question

Which equation can be used to represent “six added to twice the sum of a number and four is equal to one-half of the difference of three and the number”?

6 + 2(x + 4) = (3 – x)
6 + 2(x + 4) = (x – 3)
(6 + 2)(x + 4) = (3 – x)
(6 + 2)(x + 4) = (x – 3)

in progress 0
Charlie 2 days 2021-10-10T23:30:03+00:00 2 Answers 0

Answers ( )

    0
    2021-10-10T23:31:05+00:00

    I would say its option (a)

    But I’m confused why you put the one-half there, since I don’t see any halves.

    Steps

    Six added

    6 +

    to twice

    6 + 2()

    the sum of a number and four

    6 + 2(x + 4)

    is equal to

    6 + 2(x + 4) =

    The difference of three and the number.

    6 + 2(x + 4) = (3 – x)

    0
    2021-10-10T23:31:22+00:00

    Answer:

    a. 6 + 2(x + 4) = (3 – x)

    Step-by-step explanation: just took the test

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )